Editorial: Roles of the Circadian Rhythms in Metabolic Disease and Health - Letizia Galasso; Lucia Castelli; Eleonora Bruno (Metabolites)
Chronobiology is the field of study focused on understanding the temporal patterns of biological functions, specifically examining the regular cycles or oscillations in these processes [...]